The taming of the shrew - Shakespeare, William, 1564-1616 (Shakespeare, William, 1564-1616. No fear Shakespeare., 2004)
Presents the complete text to William Shakespeare's play "The Taming of the Shrew" with an easy-to-understand translation on facing pages, helping students better understand the work and its meaning.